Pulsed Current Activated Rapid Sintering of Binderless Nanostructured TiC and WC and Their Properties - Kwak, Bong-Won; Yoon, Jin-Kook; Shon, In-Jin (AMER SCIENTIFIC PUBLISHERS, 2017)
The rapid sintering of nanostructured TiC and WC hard materials in a short time was investigated with pulsed current activated sintering process. The advantage of this process is that it allows very quick densification to near theoretical density and prohibition of grain growth in nanostructured materials. A dense nanostructured TiC and WC hard material with a relative density of up to 98% was produced with simultaneous application of 80 MPa pressure and pulsed current of 3000 A within two minutes. The sintering behavior, microstructure and mechanical properties of binderless TiC and WC were investigated.
Keywords: MECHANICAL-PROPERTIES; MICROSTRUCTURE; CONSOLIDATION; CARBIDES